Ileocecal Anastomosis Type Significantly Influences Long‐Term Functional Status, Quality of Life, and Healthcare Utilization in Postoperative Crohn's Disease Patients Independent of Inflammation Recurrence. (April 2018) - Gajendran, Mahesh; Bauer, Anthony J; Buchholz, Bettina M; Watson, Andrew R; Koutroubakis, Ioannis E; Hashash, Jana G; Ramos‐Rivers, Claudia; Shah, Nilesh; Lee, Kenneth K; Cruz, Ruy J; Regueiro, Miguel; Zuckerbraun, Brian; et al.
Abstract : OBJECTIVES: Anastomotic reconstruction following intestinal resection in Crohn's disease (CD) may employ side‐to‐side anastomosis (STSA; anti‐peristaltic orientation) or end‐to‐end anastomosis (ETEA). Our aim was to determine the impact of these two anastomotic techniques on long‐term clinical status in postoperative CD patients. METHODS: We performed a comparative effectiveness study of prospectively collected observational data from consented CD patients undergoing their first or second ileocolonic bowel resection and re‐anastomosis between 2008 and 2012, in order to assess the association between anastomosis type and 2‐year postoperative quality of life (QoL), healthcare utilization, disease clinical or endoscopic recurrence, use of medications, and need for repeat resection. RESULTS: One hundred and twenty eight postoperative CD patients (60 STSA and 68 ETEA) were evaluated. At 2 years postoperatively, STSA patients had higher rates of emergency department visits (33.3% vs. 14.7%; P =0.01), hospitalizations (30% vs. 11.8%; P =0.01), and abdominal computed tomography scans (50% vs. 13.2%; P <0.001) with lower QoL (mean short inflammatory bowel disease questionnaire 47.9 vs. 53.4; P =0.007). There was no difference among the two groups in the 30 day surgical complications and 2‐year patterns of disease activity, CD medication requirement, endoscopic recurrence, and need for new surgical management (all P  > 0.05). CONCLUSIONS: At 2 years postoperatively, CD patients with ETEA demonstrated better QoL and less healthcare utilization compared with STSA, despite having similar patterns of disease recurrence and CD treatment. These findings suggest that surgical reconstruction of the bowel as an intact tube (ETEA) contribute to improved functional and clinical status in patients with CD.